Relaciones de duración y divisibilidad del reglamento contractual: apuntes para una reconceptualización - Longobucco, Francesco (2017)
The essay analyzes the role that time plays in the single specific transaction, in order to revisit the classic category of long-term contracts. In this perspective, considering the variety of interests involved, the author reexamines the structuralist traditional concept of durable obligations related to a continuing and repeated prevision, aiming to associate long-term contracts mainly to the functional divisibility of the whole contract itself, to the concrete cause realized by negotiation through the time, to a dynamic consideration of the interests that parties would achieve through the duration. Therefore, the main idea of the proposed analysis is that a careful investigation only of the contractual interests of the parties, aside from any abstract and typological approach, can offer a convincing way of solving problems about the still discussed nature of long-term contracts.